FRI0147 Anti-mÜllerian hormone levels in female rheumatoid arthritis patients trying to conceive – the role of ovarian function in time to pregnancy in a nationwide cohort study. (15th June 2017) - Brouwer, J; Laven, JS; Hazes, JM; Visser, JA; Dolhain, RJ
Abstract : Background: Subfertility, a time to pregnancy (TTP) >12 months, is present in 40% of women with rheumatoid arthritis (RA) actively trying to conceive. 1 Since RA patients appear to reach menopause at a younger age 2, the reduced fertility may be caused by a lower ovarian reserve (OR). Serum anti-Müllerian hormone (AMH) levels are currently the most reliable way to measure the OR. Objectives: Our objective was to study preconception AMH levels and their association with TTP in women with RA. Methods: A post-hoc analysis was performed in patients of the Pregnancy-induced Amelioration of RA (PARA) cohort who were visited preconceptionally. Serum AMH levels were measured using the pico AMH ELISA assay (Ansh Labs, Texas, USA), and compared to converted 3 AMH values from a cohort of 554 healthy adult controls 4 . Results: Preconception serum was available in 209 women aged 32.1±3.9 years, of whom 45% were subfertile. The median AMH level was 2.5 ug/L (IQR 1.5–4.6). AMH levels were significantly lower compared to healthy controls (p<0.001), with 17.2% (95% CI 10.7 – 23.8%) of patients having levels below the age-specific 10th percentile. Log-transformed AMH levels were negatively associated with age (-0.070 (95% CI -0.11;-0.031), p=0.001), and with the presence of anti-citrullinated protein antibodies (ACPA) (-0.38 (95% CI -0.71;-0.056), p=0.022). The associations remained significant in the multivariable analyses. AMH levels showed no significant association with TTP (HR 1.09 (95% CI 0.94;1.27), p=0.26). Conclusions: Women with RA have lower AMH levels than healthy controls. Reduced AMH levels were more pronounced in ACPA positive patients, suggesting that the OR may be compromised more strongly in patients with a more severe disease. However, since preconception AMH levels were not associated with TTP, the reduced levels do not explain the reduced fertility in women with RA. References: Brouwer J, Hazes JM, Laven JS, Dolhain RJ. Fertility in women with rheumatoid arthritis: influence of disease activity and medication. Ann Rheum Dis 2015;74:1836–41. Del Junco DJ, Annegers JF, Coulam CB, Luthra HS. The relationship between rheumatoid arthritis and reproductive function. Br J Rheumatol 1989;28 Suppl 1:33; discussion 42–5. Su HI, Sammel MD, Homer MV, Bui K, Haunschild C, Stanczyk FZ. Comparability of antimullerian hormone levels among commercially available immunoassays. Fertil Steril 2014;101:1766–72 e1. Lie Fong S, Visser JA, Welt CK, et al. Serum anti-mullerian hormone levels in healthy females: a nomogram ranging from infancy to adulthood. J Clin Endocrinol Metab 2012;97:4650–5. Acknowledgements: This study was funded by the Dutch Arthritis Foundation (Reumafonds). The pico AMH assays were generously provided by Ansh Labs (Houston, Texas, USA). Furthermore, we would like to thank all patients and rheumatologists who contributed to the PARA study, as well as all researchers and laboratory workers who worked on this project. Disclosure of Interest: J. Brouwer: None declared, J. Laven: None declared, J. Hazes: None declared, J. Visser: None declared, R. Dolhain Grant/research support from: unrestricted research grant by UCB Pharma BV